SMART-технології у вищій освіті - Скляр, Радміла Вікторівна; Скляр, Радмила Викторовна; Skliar, Radmila; Дереза, Олена Олександрівна; Дереза, Елена Александровна; Dereza, Olena (My University, 2020)
UK: В статті досліджено умови реалізації SMART-технологій в освітньому процесі закладів вищої освіти. Розкрито концепцію SMARTосвіти, умови її реалізації та доказано, що на сучасному етапі найбільш перспективною є модель комбінування традиційної і SMART-освіти. EN: The article investigates the conditions for the implementation of SMART-technologies in the educational process of higher education institutions. The concept of SMART-education, the conditions of its realization are revealed and it is proved that at the present stage the most promising model is the combination of traditional and SMART-education.
SMART-technologies in higher education
Keywords: SMART-технології; SMART-освіта; освітній процес; здобувачі вищої освіти; викладач; вища освіта; компетентності; інформація; SMART-technologies; SMART-education; educational process; applicants for higher education; teacher; higher education; competences; information